The Effects of Thinking Styles and Inventive Problem-Solving on the Problem-Solving Skills for Design and Technology Students - Abd Nasir, Nuraliah; Tze Kiong, Tee; Sai'en, Shanty; Qi, Wang; Azid, Nurulwahida; Swaran Singh, Charanjit Kaur; Ichwanto, Muhammad Aris; Juhari, Mohamad Ikhwan (Journal of Technical Education and Training, 2023)
The Creative Critical Thinking Skills Model aims to apply a critical and creative thinking style to students so that they can solve inventive problems well. However, teachers overlook the importance of this thinking style because they focus on inventive problem solving. Thus, a teaching module based on the Meyer Model has been developed to help teachers teach inventive problem-solving skills. This module has been developed by combining critical and creative thinking styles and the Theory of Inventive Problem Solving (TRIZ) which is a theory that uses structured and systematic methods to solve inventive problems. This study aims to evaluate the effect of module implementation on the achievement of Inventive Problem-Solving Skills of standard four Design and Technology students in five aspects (i) problem situation (ii) problem cause (iii) strategy and approach (iv) solvability (v) innovation. This study used a quantitative approach with a quasi-experimental design. A total of 106 students were selected by cluster of random sampling and divided into 2 group which is control group (CG) and treatment group (TR). The research instrument used pre-test and post-test set to measure Inventive Problem-solving skills (IPSS) achievement. The results of the test analysis show that there is a significant improvement in the five aspects of the student’s IPSS. In conclusion, the TRIZ-based Thinking Style Module help teachers in teaching and learning in the classroom, especially in generating ideas to solve problems. The exposure of critical and creative thinking styles in this module also indirectly guides users to have a balanced style which has the potential to solve problems more effectively.